Knowledge Of Tuberculosis Among General Practitioners in Surat City - Anamika Majumdar; Kallol Mallick; Rachana Prasad; Bipin Vasava; Rajiv Kumar Prasad; Vaibhav Gharat (Medsci Publications, 2012)
Background: India's Revised National Tuberculosis Control Programme (RNTCP) has made significant progress in TB control through countrywide DOTS implementation. This also includes efforts to engage the private medical sector in TB care and control through various published schemes. Objective: To assess the knowledge of tuberculosis among the general practitioners in Surat. Methodology: It was cross-sectional conducted among general practitioner of Surat city by interview using a pretested semi-structured questionnaire during March-April 2010. Results: Out of the 28 participating general practitioners, only 8 (28.6%) claimed to be using the drugs of alternative medicine for TB treatment. 64.3%, 25% and 10% believed that TB should be diagnosed by sputum microscopy, X-ray findings and sputum culture respectively. Conclusion: Health policy managers and DOTS implementers should encourage all doctors, particularly private sector doctors, to receive RNTCP training and follow DOTS methodology. Improvement is needed in RNTCP training, and emphasis needs to be given to correct diagnosis, management and follow-up of TB patients.